WAYS OF SPIRITUAL AND MORAL REVIVAL OF A STUDENT’S PERSONALITY - Hordiyenko, S.H. (Pedagogy of Higher and Secondary Education, 2009)
Basing on theories of outstanding philosophers, educators and psychologists the author makes an attempt to outline some ways of spirinally-moral revival of a student’s personality taking into account the realia of today - the crisis of spirituality of the society.